Characterization of marigold genotypes under Bihar conditions - Priyanka Kumari; Deepti Singh (Annals of Agricultural Research, 2022)
Twelve marigold genotypes were evaluated under Bihar conditions during the year 2021-22 to identify suitable varieties for commercial flower production. Genotypes namely Pusa Basanti Gainda, Hisar Beauty, Hisar Jafari-2, Sutton Orange, Brocade Mix, Sutton Yellow, Crackerjack, Bonita Bolero, Pusa Narangi Gainda, Orange Bunch, Inca Yellow and Inca Orange were selected for twelve growth and flowering traits. The experiment was laid out in Randomized Block Design (RBD) with three replications. Significant differences were recorded among different genotypes for various vegetative and repriductive attributes. Genotype Hisar Jafari-2 recorded maximum plant spread (75.45 cm), number of primary branches per plant (26.67), leaf biomass (1745.61 g), number of flowers per plant (163.00) and flower yield per plant (676.87 g), whereas maximum plant height (72.19 cm) was reported in genotype Crackerjack. Genotypes Brocade Mix attained minimum days to first first flower opening (54.78 days), wheraes genotype Pusa Narangi Gainda obtained maximum flower duration (107.22 days) and genotype Sutton Orange produced maximum flower diameter (6.84 cm).